2022
DOI: 10.3390/pharmaceutics14071497
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mucoadhesive Vehicle Based on Lyophilized Liposomes for Drug Delivery through the Sublingual Mucosa

Abstract: A pharmaceutical vehicle based on lyophilized liposomes is proposed for the buccal administration of drugs aimed at systemic delivery through the sublingual mucosa. Liposomes made of egg phosphatidylcholine and cholesterol (7/3 molar ratio) were prepared and lyophilized in the presence of different additive mixtures with mucoadhesive and taste-masking properties. Palatability was assayed on healthy volunteers. The lyophilization cycle was optimized, and the lyophilized product was compressed to obtain round an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…This result is in agreement with previously reported by De Jesús Valle and Zarzuelo Castañeda et al. who found that the drug release could be explained by the difference in molecular packing and deformability associated with the edge activator used (De Jesús Valle et al., 2022 ). The presence of Tween 80 at high concentration could improve the drug’s solubility by raising nano-spanlastic bilayer fluidity, resulting in an improvement of membrane permeability and hence, forward improving the release rate (Al-Mahallawi et al., 2014 ).…”
Section: Resultssupporting
confidence: 93%
“…This result is in agreement with previously reported by De Jesús Valle and Zarzuelo Castañeda et al. who found that the drug release could be explained by the difference in molecular packing and deformability associated with the edge activator used (De Jesús Valle et al., 2022 ). The presence of Tween 80 at high concentration could improve the drug’s solubility by raising nano-spanlastic bilayer fluidity, resulting in an improvement of membrane permeability and hence, forward improving the release rate (Al-Mahallawi et al., 2014 ).…”
Section: Resultssupporting
confidence: 93%
“…The acceptor compartment was filled with 20 mL of phosphate-buffered saline (PBS) at pH 7.4 and 37 ± 0.5 • C with 250 rpm stirring (Figure S4, Supplementary Materials). These buffer solutions represent the physiological conditions under which the drug is released and permeates the membrane (n = 3) [17,19,55]. At each hour interval, 1 mL of samples were collected from the acceptor compartment and replaced with fresh PBS.…”
Section: Permeapad ® Permeation Testmentioning
confidence: 99%
“…Compared to oral administration, sublingual administration can increase drug absorption by 3-10 times, with only hypodermic shots exceeding it [15]. However, several variables may restrict drug absorption via the sublingual mucosa, including a small area for absorption, tongue movement causing shearing forces, short residence duration due to rapid turnover of saliva, involuntary swallowing of fluids greater than 200 µL, and/or involuntary swallowing of the dosage forms [10,13,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation